2001
DOI: 10.1590/s0103-50532001000600017
|View full text |Cite
|
Sign up to set email alerts
|

Fe (III) - Galactomannan Solid and Aqueous Complexes: Potentiometric, EPR Spectroscopy and Thermal Data

Abstract: Galactomananas podem ser empregadas como aditivos na indústria alimentícea para modificar a viscosidade do produto final. Como não são absorvidas pelo organismo humano, sua adição a alimentos dietéticos é muito promissora. Os equilíbrios entre Fe(III) e galactomananas e arabinogalactana de várias leguminosas foram caracterizadas por titulações potenciométricas e espectroscopia de EPR. Os logaritmos das constantes de equilíbrio para a formação dos complexos ML (M = Fe(III) e L = unidade monomérica dos biopolíme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
2
8
0
2
Order By: Relevance
“…The potentiometric titrations were carried out in duplicate, according to the methodology developed in the Chemical Equilibrium Laboratory-LEQ-UFPR [24][25][26] for biopolymers, in a Micronal pH meter (Brazil, model B-374) with a glass electrode H 3 O + sensitive (AnalyserBrazil, model SM01), and a saturated calomel reference electrode (Analyser-Brazil, model SR 02). The potentiometric apparatus was calibrated with standard HCl and KOH (Merck, Brazil) solutions in order to read -log [H + ] directly.…”
Section: Potentiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The potentiometric titrations were carried out in duplicate, according to the methodology developed in the Chemical Equilibrium Laboratory-LEQ-UFPR [24][25][26] for biopolymers, in a Micronal pH meter (Brazil, model B-374) with a glass electrode H 3 O + sensitive (AnalyserBrazil, model SM01), and a saturated calomel reference electrode (Analyser-Brazil, model SR 02). The potentiometric apparatus was calibrated with standard HCl and KOH (Merck, Brazil) solutions in order to read -log [H + ] directly.…”
Section: Potentiometrymentioning
confidence: 99%
“…19 Studies in the literature involved absorption of metal ions in chitosan, [20][21][22] but complete equilibrium investigations with determination of binding constants, as well as pH speciation, have only recently been addressed in the literature. [23][24][25][26] Also, the reported studies presented different experimental conditions from this present work.…”
Section: Introductionmentioning
confidence: 99%
“…The protonation is due to the HO-6 group, which is the only one acidic enough to release or uptake a proton in the aqueous equilibrium and its value is very close to that for primary alcohols [61][62][63]. A previous study about mannan and galactomannan showed that the protonation constant of C-6-O À can vary from K = 1.17 ± 0.04 Â 10 9 to K = 3.39 ± 0.05 Â 10 9 , respectively [12,18].…”
Section: Potentiometric Titrationmentioning
confidence: 85%
“…The thermal behavior of the calcium complex was completely different from that of HLC with respect to the loss of mass and the temperature intervals in which it took place, indicating the formation of a new chemical compound with more stable thermodynamic properties [33]. The first dehydration range of the HLC-Ca complex lies between 35°C and 238°C.…”
Section: Thermogravimetric Analysismentioning
confidence: 88%